Factors Influencing Consumers in Making Purchases - Sudiyono; Abdul Aziz (PT FORMOSA CENDEKIA GLOBAL, 2023)
One of the causes of traffic congestion is the increase in the number of vehicles that are not matched by the expansion of existing roads. Traffic congestion is a problem in almost all countries in the world. This research was conducted to find out what factors can influence consumers in making purchases of a product in meeting their needs. Multiple regression analysis was used in this study to examine the relationship between variables. From the test results it is known that the partial analysis of variable X (E-service, Personal Driver Services, and Customer Experience) has a positive and significant effect on variable Y (Customer Satisfaction). The Sobel test shows that the role of consumer satisfaction as a moderating variable has a positive effect, and the results of the partial analysis of variable X (Eservice, Personal Driver Services), and Customer Experience on variable Y (Shopping Intentions) have a positive effect. and significant influence